KONDISI FISIOLOGIS, PROFIL DARAH DAN STATUS MINERAL PADA INDUK DAN ANAK KAMBING PERANAKAN ETAWAH (PE) (Physiological Conditions, Blood Profile and Mineral Statues of Kid and Doe Etawah Crossbred) - Ella Rosita; Idat Galih Permana; Toto Toharmat; Despal Despal (Buletin Ilmu Makanan Ternak, 2015)
Peranakan Etawah goat (PE) is one of dairy goats type which are developed in Indonesia for them well adapted to Indonesian climate. The pregnant doe and kid goat require higher nutrients making it more susceptible to health problems. This study aimed to learn the health statues of pregnant doe and kid goat Etawah Crossbred that rise in farm through the physiological condition, blood profile, and the minerals calcium and phosphorus statues. This study used 12 pregnant does and 11 kid goat. The results showed that calcium (143.03 and 0.11 ppm) and phosphorus (161.45 and 0.24 ppm) contents in pregnant doe blood was lower than the kid. Physiological condition in pregnant doe was normal range, but the blood profile of kid goat was higher than the parent. It is concluded that kid goat’s health statues was not better than the parent when viewed from the physiological condition and blood profile, but the mineral content of the kid was better than its parent.Keywords: growth of livestock, minerals elements Ca and P, physiological condition.